Education for a Culture of Peace and Co-Existence - Silvia Guetta (Firenze University Press, 2016)
Education is a key and fundamental tool required to achieve social change, especially regarding social cohesion and co-existence. Education affects the most critical issues facing humanity, including the proliferation of various forms of violence, environmental degradation, and annihilation of cultures. I argue that the impact of education is equal to that of economics, politics, and technological advances. Therefore, if we wish to see change, educational reform has to be designed to operate in a global-human context, empowering and allowing people to achieve their potential. It should instil in individuals and groups respect for others with whom they interact, in a global as well as local sense. The article draws on the theories of Edgar Morin, Reuven Feuerstein, and Jerome Bruner, and their contributions to the development of educational approaches that encourage a culture of responsible, participatory, and creative coexistence. .